Masked observation for majority-based control of a democratic progress model in the framework of discrete event systems - Park, Seong Jin; Yang, Jung Min (Asian Journal of Control, 2021)
This paper addresses a simple democratic progress model represented by a discrete-event system (DES) and the influence of information accessibility on the progressiveness of the model. Each agent makes a decision according to its selfish criterion, and the final decision for the progress or regression of the system is done by the majority rule based on individual decisions of agents. We first present the conditions for the closed-loop system to be progressive or regressive under full observation where every agent can observe all the states. Then we focus on the masked observation problem, namely, whether the progressiveness of the closed-loop behavior can be changed by restricting the information accessibility of agents that are characterized by their masks. Especially, we show that due to the elite class, the regressive closed-loop system can never be transformed into progressive regardless of mask design, which conforms to the feature of modern democracy.
Keywords: Closed-loop behavior; Final decision; Information accessibility; Majority rule; Mask design; automaton; democracy; discrete event systems (DESs); masked observation; supervisory control